2020
DOI: 10.1002/mnfr.202000798
|View full text |Cite
|
Sign up to set email alerts
|

Salted and Unsalted Zhàcài (Brassica juncea var. tumida) Alleviated High‐Fat Diet‐Induced Dyslipidemia by Regulating Gut Microbiota: A Multiomics Study

Abstract: Scope Zhàcài (ZC), a salting‐processed Brassica juncea var. tumida vegetable, is widely consumed as a pickle, but little is known about the health benefits of both salted and unsalted ZC as a whole food. Methods and Results The preventive effects of salted and unsalted ZC against dyslipidemia are assessed in high‐fat (HF) diet‐fed mice. HF intake for 12 continuous weeks cause dyslipidemia in mice, as evidenced by the elevations in serum total triglyceride, total cholesterol, and low‐density lipoprotein cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…[ 22 ] Recent evidence has suggested that the intake of whole plant‐based foods, such as Zhàcài and bitter melon, could reduce the risk of obesity and associated metabolic disease. [ 7,9 ] In line with these findings, daily supplementation with whole AC also effectively alleviated the impairment of glucose tolerance, lipid disorder, and hepatic injury in HFD‐induced obese mice. Accordingly, we speculated that prolonging the treatment period or increasing the dosage of AC for HFD mice might result in a significant decrease in body weight while reducing adipocyte size.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[ 22 ] Recent evidence has suggested that the intake of whole plant‐based foods, such as Zhàcài and bitter melon, could reduce the risk of obesity and associated metabolic disease. [ 7,9 ] In line with these findings, daily supplementation with whole AC also effectively alleviated the impairment of glucose tolerance, lipid disorder, and hepatic injury in HFD‐induced obese mice. Accordingly, we speculated that prolonging the treatment period or increasing the dosage of AC for HFD mice might result in a significant decrease in body weight while reducing adipocyte size.…”
Section: Discussionmentioning
confidence: 59%
“…[ 4,5 ] Moreover, several studies have addressed some gut bacteria alleviate obesity and metabolic dysfunctions partially depending on their metabolites. [ 6,7 ] For these reasons, targeting the manipulation of microbiota and associated metabolites may be an effective approach for preventing obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that after chronic HSD feeding, the intestinal flora of mice was significantly changed, the abundance of Alistipes and Ruminococcaceae UGg-009 in the gut was increased, and that of intestinal Lactobacillus was decreased dramatically [35]. Li reported that feeding mice pickles with salt disrupted the metabolism of short-chain fatty acids and the intestinal flora [36]. Similar results were found in our study.…”
Section: Discussionsupporting
confidence: 89%
“…[ 50 ] SCFAs, the main end products of carbohydrate degradation by gut microbiota, regulated lipid metabolism in the liver to improve hyperlipidemia and glycemia. [ 16 ] Among them, administration of acetate and propionate lessen blood glucose in diabetic mice and healthy rats. [ 51 ] In fact, in our study, CE treatment had a significantly positive regulatory effect on the content of acetic acid and propionic acid, and the contents of these two acids were positively correlated with the relative abundance of Verrucomicrobiaceae and Akkermansia .…”
Section: Discussionmentioning
confidence: 99%
“…[14] Fortunately, plants and their extracts can reduce body weight and improve insulin resistance by enriching specific intestinal bacteria and promoting the production of microbial-derived metabolites. [15,16] However, reports on chickpea extract (CE) in this regard are limited. The purpose of the present work was to establish a T2DM model induced by HFD and streptozotocin to elaborate the effects of chickpeas on intestinal flora and metabolomics.…”
Section: Introductionmentioning
confidence: 99%